Identifikasi Cacat pada Las Pipa Stainless Steal Berdasarkan Film Hasil Uji Radiografi - Joandris, Septiara Canprisa; Nisa, Safira J; Nurhasanah, Tita; Murti, Wahyu S; Suponco, Wahyu; Mulyono, Tasih (UNIVERSITAS SERAMBI MEKKAH, 2024)
Pipe welding has the potential to experience defects. Thus, identification of defects in pipe welding needs to be carried out in order to minimize work accidents and ensure the quality of the weld. Identification of this welding defect is carried out by X-ray irradiation on stainless steel pipes and films, washing radiographic films, reading radiographic films. The results obtained are . Film1 cannot be accepted because there are artifacts in the film image results even though it shows welding defects in the form of incomplete penetration and gas pore. While film 2 can be accepted because it meets all the requirements with the presence of defects in the weld, namely Clustered Porosity. Identification of pipe defects has results that are not in accordance with standards so that repairs need to be repair.